Sustainability in the context of natural and social environments.: An actor-oriented interpretation from South-West Tanzania - Tröger, Sabine (ERDKUNDE, 2002)
Sustainable use of the natural environment is conventionally interpreted as a result of the successful or unsuccessful adaptation of the human being to the natural environment, whereby factors such as 'knowledge' and 'structural conditions' are taken to be decisive in the success of efforts to adapt. In contrast to this kind of interpretation, this paper takes the influence of social factors on people's activities into account. People's adaptation to the natural environment is shown from the perspective of structural theories as a variable within human actions that orient themselves according to the actors' perceptions of everyday life, which in turn are subject to historical change. Using examples drawn from the Ufipa Plateau in South-west Tanzania, the paper illustrates how a historical re-valuation of 'labour', from a 'use value for food security' to an 'exchange value on the market', and the accompanying re-valuation of the 'effort involved in labour in the fields' has affected people's actions, and how the use of the natural resources is affected by this re-valuation on different levels. Tanzania has experienced two fundamental social transformations in the last 30 years, and it appears that these multiple changes have been accompanied by a loss of confidence among the population that largely rules out practical consciousness as a guide for routine activities. Dependent on their level of reflection on the social consequences of the changes in the community, the actors can influence their vulnerability to food shortages and thus ultimately on the sustainability of their livelihood as a whole. Through their actions, they can create new conditions for the use of the natural environment.